Dinar and Dirham as Sharia-Based Monetary Solutions in Indonesia - Kholiq, Mairummah; Khusnudin (al-Afkar, Journal For Islamic Studies, 2025)
The current global monetary system is dominated by fiat currencies which depend on monetary policy and state trust, but this also presents challenges such as inflation, exchange rate instability and the potential for economic crises. As a more stable alternative and in accordance with sharia principles, the use of dinars and dirhams, which are based on the precious metals gold and silver, is gaining attention. Dinars and dirhams have a long history in Islamic civilization, starting from the time of the Prophet Muhammad SAW, and have been proven to have stable intrinsic value and are free from the practice of usury. This currency can also reduce dependence on fiat currencies which are vulnerable to inflation and speculation. This research aims to explore the potential and challenges of implementing the dinar and dirham as a sharia-based monetary system in Indonesia, using a qualitative approach based on literature review. Dinars and dirhams offer advantages such as value stability, economic resilience to the global crisis, and simplicity in the financial system. Apart from that, they can also function as a tool to support sharia economic growth, strengthen transactions in society, and encourage the development of small and medium businesses. However, the main challenges in its implementation include the need for clear regulations, low levels of public understanding, and limited infrastructure to support the production and distribution of precious metals. With increasing public awareness of sharia economics and the support of digital technology, dinars and dirhams have great potential to be implemented as alternative monetary solutions that are sustainable and fair, supporting economic stability in Indonesia.